Effect of optical technical of guiding emmetropization lenses on myopia prevention in children without myopia - Zhao, Qi; Li, Jiaqi; Liang, Tiangang; Cheng, Jie; Nie, Weixiang; Wang, Yanhua (Scientific reports, 2025)
Accelerated emmetropization may result in premature onset of myopia. And there is a lack of reports on the effect of peripheral defocus spectacle lenses in non-myopia children. The purpose of this study was to investigate the significance of preventing myopia using Optical Technical Of Guiding Emmetropization (O.T.O.G.E.) lenses in non-myopic children aged 5–8 years. This non-randomized controlled study enrolled 110 non-myopic children aged 5–8 years. Participants were assigned to two groups. One group (experimental group, 55 eyes) wore O.T.O.G.E. lenses, while the other group (control group, 55 eyes) wore no spectacles. Refractive outcomes and axial length (AL) were measured in all subjects and then again six months and one year later for comparison. T-tests were used to compare the growth of spherical equivalent refraction (SE) and AL between the two groups. At the end of six months, the experimental group had less SE myopic shift and AL elongation than the control group (0.01 ± 0.20D vs. 0.32 ± 0.38D, 0.08 ± 0.06 mm vs. 0.19 ± 0.09 mm, respectively) ( P < 0.01). Moreover, at the end of one year, the experimental group had less SE myopic shift and AL elongation than the control group (0.26 ± 0.26D vs. 0.55 ± 0.59D, 0.21 ± 0.09 mm vs. 0.44 ± 0.20 mm, respectively) ( P < 0.01). Wearing O.T.O.G.E. lenses in non-myopic children aged 5–8 years attenuated hyperopic reduction, slowed AL elongation, and delayed myopia onset.